Geologic Setting of Eclogite-facies Assemblages in the St. Cyr Klippe, Yukon–Tanana Terrane, Yukon, Canada - Petrie, Meredith Blair; Gilotti, Jane A.; McClelland, William C.; van Staal, Cees; Isard, Sierra J. (Geoscience Canada, 2015)
The St. Cyr area near Quiet Lake hosts well preserved to variably retrogressed eclogite found as sub-metre to hundreds of metre-long lenses within quartzofeldspathic schist in south-central Yukon, Canada. The St. Cyr klippe consists of structurally imbricated, polydeformed and polymetamorphosed units of continental arc crust and ultramafic–mafic rocks. Eclogite-bearing quartzofeldspathic schist forms thrust slices in a 30 km long by 6 km wide, northwest-striking outcrop belt. The schist unit comprises metasedimentary and felsic intrusive rocks that are intercalated on the metre to tens of metres scale. Ultramafic rocks, serpentinite and associated greenschist-facies metagabbro form imbricated tectonic slices within the eclogite-bearing quartzofeldspathic unit, which led to a previously held hypothesis that eclogite was exhumed within a tectonic mélange. The presence of phengite and Permian zircon crystallized under eclogite-facies metamorphic conditions in the quartzofeldspathic host rocks indicate that the eclogite was metamorphosed in situ together with the schist as a coherent unit that was part of the continental arc crust of the Yukon–Tanana terrane, rather than a mélange associated with the subduction of oceanic crust of the Slide Mountain terrane. Petrological, geochemical, geochronological and structural similarities link St. Cyr eclogite to other high-pressure localities within Yukon, indicating the high-pressure assemblages form a larger lithotectonic unit within the Yukon–Tanana terrane. RÉSUMÉ La région de St-Cyr renferme des éclogites bien conservées à légèrement rétrogradées qui se présentent sous forme de lentilles allant de la fraction de mètre à quelques centaines de mètres de longueur, au sein d’un schiste quartzofeldspathique du centre-sud du Yukon au Canada. La klippe de St-Cyr est structurellement constituée d’unités imbriquées, polydéformées et polymétamorphisées de croûte d’arc continental et de roches ultramafiques à mafiques. Les schistes quartzofeldspathiques à lentilles d’éclogites forment des écailles de chevauchement d’une bande de 30 km de longueur par 6 km de largeur de direction nord-ouest. Les schistes sont constitués de roches métasédimentaires et de roches intrusives felsiques intercalées à des intervalles qui vont du mètre à quelques dizaines de mètres. Les roches ultramafiques, serpentinites et métagabbros au facies à schiste vert forment des écailles tectoniques imbriquées au sein de l’unité quartzofeldspathique à lentilles d’éclogite, d’où une précédente hypothèse voulant que les éclogites soient un produit d’exhumation à partir d’un mélange tectonique. La présence de phengite et de zircon permien cristallisé sous conditions métamorphiques du faciès à éclogite au sein de la roche hôte quartzofeldspathique indiquent que l’éclogite a été métamorphisée en place, avec le schiste comme unité cohérente du terrane de croûte d’arc continental de Yukon–Tanana, plutôt qu’un mélange associé à une subduction de croûte océanique du terrane de Slide Mountain. Des similarités pétrologiques, géochimiques, géochronologiques et structurales lient les éclogites de St-Cyr à d’autres lieux de hautes pressions au Yukon, ce qui indique que les assemblages de hautes pressions forment une unité lithotectonique plus grande au sein du terrane de Yukon–Tanana.